Abies holophylla Leaf Essential Oil Alleviates Allergic Rhinitis Based on Network Pharmacology - Jae Yoon Chung; Nayoung Park; Mi Hye Kim; Woong Mo Yang (MDPI AG, 2023)
Abies holophylla is an evergreen coniferous species that has been widely used for treating pulmonary diseases and colds. Previous research has demonstrated the anti-inflammatory effect of Abies species and the anti-asthmatic activities of Abies holophylla leaf essential oil (AEO). As asthma and allergic rhinitis (AR) share pathophysiology and pharmacotherapeutic interventions, AEO inhalation can also ameliorate upper respiratory allergic diseases. This study explored the protective effects of AEO on AR with network pharmacological pathway prediction. The potential target pathways of AEO were analyzed by a network pharmacological approach. The BALB/c mice were sensitized by ovalbumin (OVA) and 10 μm particular matter (PM10) to induce allergic rhinitis. Aerosolized AEO 0.0003% and 0.03% were delivered by nebulizer for 5 min a day, 3 times a week for 7 weeks. Nasal symptoms (sneezing and rubbing), histopathological changes in nasal tissues, serum IgE, and zonula occludens-1 (ZO-1) expressions on nasal tissues were analyzed. After AR induction with OVA+PM10 and inhalation of AEO 0.0003% and 0.03% treatment, AEO significantly decreased allergic symptoms (sneezing and rubbing), hyperplasia of nasal epithelial thickness, goblet cell counts, and serum IgE level. The network analysis demonstrated that the possible molecular mechanism of AEO is highly associated with the IL-17 signaling pathway and tight junction. The target pathway of AEO was investigated in RPMI 2650 nasal epithelial cells. Treatment of AEO on PM10-treated nasal epithelial cells significantly reduced the production of inflammatory mediators related to the IL-17 signaling pathway, NF-κB, and the MAPK signaling pathway and prevented the reduction in TJ-related factors. When taken together, AEO inhalation may be considered as a potential treatment for AR by alleviating nasal inflammation and recovering the tight junction.